THE THEOLOGICAL MESSAGE OF Q.S. AN-NAS IN THE BOOK MAFATIH AL-GHAYB BY FAKHRUDDIN AR-RAZI AND ITS RELEVANCE TO CONTEMPORARY LIFE - Nor Afifah; Mahda; Nismah Sa'adah; Cecep Zakarias El Bilad; Akhmad Dasuki; Imam Khomaeni Hayatullah (STKQ Al-Hikam Depok, 2026)
This study examines the theological messages of Surah An-Nas in Mafa>ti>h al-Ghayb by Fakhruddin al-Razi and their relevance to contemporary life. The background of this research is based on the increasing psychological problems, social pressures, and complex flows of information in modern society, which are closely related to the concept of al-waswa>s al-khanna>s in Surah An-Nas. This research employs a qualitative library research method with theological and contextual approaches. The primary source of this study is Mafa>ti>h al-Ghayb, while secondary sources consist of relevant books and scholarly articles. The data were analyzed descriptively and analytically through examining the meanings of the verses and al-Razi's interpretations. The findings reveal that Surah An-Nas contains three main theological concepts: Rabb, Ma>lik, and Ila>h, which represent Allah's nurturing care, sovereignty, and the exclusive right to be worshipped. In addition, the concept of al-waswa>s al-khanna>s is understood as subtle disturbances affecting the human inner self, originating from both jinn and humans. In the contemporary context, the message of this surah remains relevant as a spiritual foundation for dealing with anxiety, social manipulation, hoaxes, and distractions in the digital era. Therefore, Surah An-Nas functions not only as a prayer for protection, but also as a theological and psychological framework for maintaining the inner resilience of modern human beings.